NILAI-NILAI KEARIFAN LINGKUNGAN DALAM NOVEL SERIAL ANAK-ANAK MAMAK KARYA TERE LIYE (KAJIAN ECOCRITICISM) - Ahmad Nizarul Fanani (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This research is motivated by literature in terms of ecology and invites readers to always maintain environmental sustainability by preserving the values ofenvironmental wisdom through the reading of literary works. This study aims to determine the values of environmental wisdom contained in the novel Serial Anak-anak Mamak by Tere Liye. This research uses descriptive qualitative research method. The data in this research are sentence of the values of environmental wisdom contained in novel Serial Anak-Anak Mamak by Tere Liye which consists of four novels namely novel Burlian (2009), Pukat (2010), Eliana (2011), and Amelia (2013) all of them published by Republika Publisher. Data collection techniques in this study is to use literature techniques, techniques refer, and record techniques. Data analysis is the analysis of description and content analysis. Research results include environmental wisdom values in the form of respect for nature, a sense of common ownership of the community to maintain natural resources, local knowledge systems to solve problems, appropriate and efficient technologies in accordance with local conditions, system of law enforcement rules, and harvest distribution mechanisms.